Millet seed oil activates β–catenin signaling and promotes hair growth - Lee, Eunyoung; Seo, Hyo-Deok; Kim, Daedong; Park, So-Hyun; Kim, Soo Ro; Hyun, Changhun; Hahm, Jeong-Hoon; Ha, Tae-Youl; Ahn, Jiyun; Jung, Chang Hwa (Frontiers in Pharmacology, 2023)
Alopecia, regardless of gender, exacerbates psychological stress in those affected. The rising prevalence of alopecia has fueled a research interest in preventing hair loss. This study investigates the potential of millet seed oil (MSO) in promoting the proliferation of hair follicle dermal papilla cells (HFDPC) and stimulating hair growth in animals with testosterone-dependent hair growth inhibition as part of a study on dietary treatments to improve hair growth. MSO-treated HFDPC significantly increased cell proliferation and phosphorylation of AKT, S6K1, and GSK3β proteins. This induces β-catenin, a downstream transcription factor, to translocate to the nucleus and increase the expression of factors related to cell growth. In a C57BL/6 mice model in which hair growth was inhibited by subcutaneous testosterone injection after shaving the dorsal skin, oral administration of MSO stimulated hair growth in the subject mice by increasing the size and number of hair follicles. These results suggest that MSO is a potent agent that may help prevent or treat androgenetic alopecia by promoting hair growth.